Potency of Lobak Leaves (Raphanus sativus L. var. hortensis Back) as Anticancer and Antimicrobial Candidates (Biodiversitas Journal of Biological Diversity, 2008)
One of vegetables can preventive cancer and have been used traditionally to cure infection, such as lobak (Raphanus sativus L.). Ineffectiveness antibiotics against microbial infections were still problem until now. Types of antibiotics and anticancer agents from natural resources should be explored and developed. This study was aimed to know toxicity effect and antimicrobial activity of active fractions from lobak leaves. Toxicity study was conducted using Brine Shrimp LethalityTest (BST). Samples were prepared at the concentration of 100, 500, and 1000Î¼g/mL. Antibacterial study against Staphylococcus aureus was conducted using agar-well diffusion method at concentration 30, 40, 50, 60, 70, 80, 100%. Ethyl acetate fraction from methanol extract is the most active that had larger clear zone in S. aureus culture (10,64 mm) and insoluble ethyl acetate fraction from methanol extract is the most active against A. salina (84% death A. salina at 100 Î¼g/mL). Bioactive compounds at active fraction were identified to contain polar compounds.Key words: Raphanus sativus L., BST, Staphylococcus aureus, active fraction